ANALISIS INDEKS KEPUASAN MASYARAKAT PADA PELAYANAN PERIJINAN DI BADAN PENANAMAN MODAL DAN PELAYANAN PERIZINAN TERPADU SATU PINTU (BPMPPTSP) KABUPATEN SEMARANG - Nopiyanti, Nopiyanti; Warsono, Hardi; Rihandoyo, Rihandoyo (Journal of Public Policy and Management Review, 2015)
Measurement of Public Satisfaction Index refers to KEMENPAN No. 25 of 2004 on Public Satisfaction Index (IKM). Objective Measurement of Public Satisfaction Index is to determine the development of the unit's performance in the service of the government agency that is implemented by the relevant agencies periodically and can be used as material for their own policies in order to further improve the quality of public services. While the purpose of research measurement IKM : how the level of customer satisfaction, aware of the elements that must be improved and how to improve community satisfaction. Community Satisfaction Measurement indicator by KEMENPAN No. 25 of 2004 was Procedures, Requirements Services, Clarity Service Officers, Disciplinary Officer Service, Responsibility Service Officers, Service Officers Ability, Speed Services, Justice Getting Care, Courtesy and hospitality Officer, Fairness Care Costs, Cost Assurance Services, Assurance Services Schedule , Safety, Environment and Security Services. Based on public satisfaction measurement indicators in the Investment and Services Agency One Stop (BPMPPTSP) in Semarang Regency, Authors recommend as follows: (1) Repair Facilities and Infrastructure support services, and (2) Increased element of comfort for users permissions to create the environment conducive to the user.